2010
DOI: 10.1063/1.3291066
|View full text |Cite
|
Sign up to set email alerts
|

Electrical determination of the spin relaxation time of photoexcited electrons in GaAs

Abstract: Spin-dependent transport for photoexcited electrons in an epitaxial Fe/GaAs interface was characterized from 5 to 300 K. The presence of spin-dependent transport was confirmed at all the measured temperatures and the spin polarization across the interface is found to increase with decreasing temperature. A time-of-flight-type model based on the Dyakonov-Perel ͑DP͒ spin relaxation mechanism was employed to explain the temperature dependence, providing that the estimated spin relaxation time in GaAs is 62 ps at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Quite a few studies of the electron spin transmission from a FM into a SC, and vice versa, have been carried out [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In order to shed light on the transmission mechanism, in particular, from a SC into a FM, a tremendous approach using an optical spin orientation method was proposed by Prins et al [8], where spinpolarized photoelectrons are excited by the illumination of circular polarized light and the spin-dependent transmission across the interface was electrically detected: Circular polarized light can excite spin-polarized electrons efficiently in the SC according to the optical selection rules [11][12][13].…”
mentioning
confidence: 99%
“…Quite a few studies of the electron spin transmission from a FM into a SC, and vice versa, have been carried out [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In order to shed light on the transmission mechanism, in particular, from a SC into a FM, a tremendous approach using an optical spin orientation method was proposed by Prins et al [8], where spinpolarized photoelectrons are excited by the illumination of circular polarized light and the spin-dependent transmission across the interface was electrically detected: Circular polarized light can excite spin-polarized electrons efficiently in the SC according to the optical selection rules [11][12][13].…”
mentioning
confidence: 99%
“…circularly polarised light creates spin-polarised electrons in GaAs via the optical selection rules [3] and an FM/SC interface is employed to measure the spin polarisation electrically. Despite a large number of investigations using this technique [4,5,6,7,8,9,10], there are no theoretical calculations supporting for them, to the authors' knowledge, except for recent tight-binding calculations on an Fe/GaAs interface by Honda et al [11]. Here, we present a phenomenological model designed for these photoexcitation experiments.…”
Section: Introductionmentioning
confidence: 93%
“…Since that fi rst experiment, there have been many related studies [16,[24][25][26][75][76][77][78][79][80][81][82][83][84][85][86]. Taniyama et al [78], Steinmuller et al [79] and Park et al [86] measured the spin-dependent photocurrent for Fe/AlO x /GaAs, NiFe(Fe)/GaAs and Fe/MgO/GaAs interfaces, respectively, under forward bias with optical spin orientation.…”
Section: Experimental Studies Of Spin Transport Into Ferromagnetsmentioning
confidence: 99%
“…As the spin polarization of electrons generated by optical spin orientation is strongly dependent on the energy of the circularly polarized light due to simultaneous excitations from the split-off subband at Γ 7 , tuning of the energy of light is critical to investigating the spin-dependent photocurrent across the interface. Kurebayashi et al [80] reported the inversion of sign in the spin-dependent photocurrent signal associated with the spin fi ltering eff ect upon varying the excitation energy. However, the values of spin-dependent photocurrent reported so far are at the few percent level, in clear contrast with the large spin polarization estimated from circular polarized electroluminescence as given in the previous section.…”
Section: Experimental Studies Of Spin Transport Into Ferromagnetsmentioning
confidence: 99%